PELATIHAN MEMBACA AL-QUR’AN YANG BAIK DAN BENAR MELALUI METODE QIRA’ATI - Fitrian Prila Wardani; Devi Riri Yulyani; Tiara Ilmiyati (Universitas Muhammadiyah Manado, 2021)
Community service is carried out to the general public, and the target of the service is the al-bayyinah Muslim study group, Yosorati Village, Kec. Sumberbaru Kab. Jember. This service is in the form of training in reading the Koran properly and correctly through the Qira'ati method, the executor first surveys the field what are the current needs of the community. In an effort to popularize the Koran, currently there are various methods that are quite helpful in facilitating the process of learning to read the Koran properly and correctly. However, the general problems encountered in teaching the Koran today are: Quality of Education, Qualifications of Ustad Teachers, Uncertain Study Time, Learning Methods used are lacking/not mastered. Based on the implementation of good and correct Qur'an reading training through the Qira'ati method in Krajan Lor Hamlet, Yosorati Village, Kec. Sumberbaru Kab. Jember is the standard for the quality of learning outcomes for mothers who are not the same. Between one and another, due to differences in educational background and also the family environment, each Muslim congregation must be different in absorbing material, it shouldn't be 100% uniform. but the levels of differences that are too far apart indicate that something is lacking in the learning process, be it from the elements, teacher, means, or methods used. The development of various methods of reading the Koran at this time indeed enriches the variety of the learning process, but if the use of the method chosen by the Koran teacher or institution does not comply with the standards required by the method maker, then from the learning process to the product produced it is definitely not standard. It is often found in our society that the ratio of the teacher of the Koran to the number of students is not balanced. The number of Koran teachers is less than the students who are ready to be taught, and even then the quality of teachers is not evenly distributed, there are even ustad who are reckless because there are no Koran teachers who are ready to teach.